Can Silodosin Be Considered a Superior Substitute for Tamsulosin in Medical Expulsion Therapy for Patients with Lower Ureteral Calculi - Aqeel Ahmed, Nabiha Rizvi, Muhammad Mohsin Riaz, Syed Asad Ali, Muhammad Asif, Haleemullah, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Urinary stones, also known as calculi, are a common urological problem affecting millions of people worldwide. Medical expulsion therapy (MET) is a commonly used treatment for lower ureteral calculi. Objectives: The main objective of the study is to find the role of silodosin as a superior substitute for tamsulosin in medical expulsion therapy for patients with lower ureteral calculi. Material and methods: The study design for this research article would be a randomized controlled trial comparing the efficacy and safety of silodosin and tamsulosin in medical expulsion therapy (MET) for patients with lower ureteral calculi. Patients with lower ureteral calculi who meet the inclusion criteria will be recruited for the study. Inclusion criteria may include age over 18 years, presence of lower ureteral calculus confirmed by imaging, and willingness to participate in the study. Exclusion criteria may include previous history of ureteral surgery, contraindication to alpha-blockers, and pregnancy. Results: A total of 100 participants were randomized to receive either silodosin (n=50) or tamsulosin (n=50) for medical expulsion therapy of lower ureteral calculi. The mean age of the participants was 45 years, and 60% were male. The stone expulsion rate at 4 weeks was 80% in the silodosin group and 75% in the tamsulosin group. There was no statistically significant difference between the two groups (p=0.54). Conclusion: In conclusion, the results of this study indicate that silodosin may not be a superior substitute for tamsulosin in medical expulsion therapy for patients with lower ureteral calculi. Both drugs demonstrated similar rates of stone expulsion and time to stone passage, as well as comparable safety profiles and patient satisfaction rates. Keywords: Silodosin, Tamsulosin, Lower Ureteral Calculi